2007
DOI: 10.1073/pnas.0702093104
|View full text |Cite
|
Sign up to set email alerts
|

Single A326G mutation converts human CYP24A1 from 25-OH-D 3 -24-hydroxylase into -23-hydroxylase, generating 1α,25-(OH) 2 D 3 -26,23-lactone

Abstract: Studies of 25-hydroxyvitamin D3-24-hydroxylase (CYP24A1) have demonstrated that it is a bifunctional enzyme capable of the 24-hydroxylation of 1␣,25-(OH) 2D3, leading to the excretory form, calcitroic acid, and 23-hydroxylation, culminating in 1␣,25-(OH) 2D3-26,23-lactone. The degree to which CYP24A1 performs either 23-or 24-hydroxylation is species-dependent. In this paper, we show that the human enzyme that predominantly 24-hydroxylates its substrate differs from the opossum enzyme that 23-hydroxylates it at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 35 publications
(51 reference statements)
1
51
0
Order By: Relevance
“…In 2007, Prosser et al demonstrated that an active site mutation, A326G, converts human CYP24A1 into a complete C23 hydroxylase, likely by increasing the space available for substrate binding (20). However, there is also mounting evidence that redox partner interactions influence the substrate binding and recognition regions of P450 enzymes (21,22,26,30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2007, Prosser et al demonstrated that an active site mutation, A326G, converts human CYP24A1 into a complete C23 hydroxylase, likely by increasing the space available for substrate binding (20). However, there is also mounting evidence that redox partner interactions influence the substrate binding and recognition regions of P450 enzymes (21,22,26,30).…”
Section: Discussionmentioning
confidence: 99%
“…While calcitroic acid is excreted in urine, 1,25(OH) 2 D3-26, 23-lactone has been demonstrated to modulate vitamin D signaling by binding the vitamin D receptor (18,19). Intriguingly, this first step in the deactivation pathway is also regioselective according to species, with the human isoform hydroxylating at both C23 and C24 sites at an approximate 2:8 ratio while rat CYP24A1 is a pure C24 hydroxlase and opossum CYP24A1 is a pure C23 hydroxylase (20).…”
mentioning
confidence: 99%
“…In the VDR-null mouse, we see a complete breakdown of this autoregulation process because CYP27B1 is not suppressed by excessive 1,25-(OH) 2 D 3 by guest, on April 28, 2019 www.jlr.org Downloaded from to a calcitroic-acid product while more primitive organisms have Gly326 and show predominantly 23-hydroxylation to give a 26,23-lactone product. The functional signifi cance of two distinct pathways in different species is unknown ( 18 ).…”
Section: Other Potential 25-hydroxylasesmentioning
confidence: 99%
“…The substrate-binding pocket is formed by several secondary structures folded around the distal face of the heme-group so that the substrate can be brought to within 3.2 Å of the iron atom for hydroxylation. An analysis of the heme-ligand geometry of 49 substrate-bound crystal structures revealed the hydroxylation target carbons actually adopt a spatially conserved orientation to the heme iron, and this can be triangulated for use in docking studies ( 18 ).…”
Section: Vitamin D 3 -25-hydroxylasesmentioning
confidence: 99%
See 1 more Smart Citation